2022
DOI: 10.1039/d2ra03262g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of upconverting nanoparticles with bis(2-ethylhexyl) adipate

Abstract: A mixture of bis(2-ethylhexyl) adipate and oleic acid provides scale-up potential and speedy heating rates in the microwave-assisted organic synthesis of upconverting nanoparticles with tunable size, crystallinity, and hydrophilic character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Notably, both these hotplates have different temperature-cotrol logic which cannot be matched. Heating rate is known to be an important parameter in UCNP synthesis [69,70]. Indeed, a recent exemplary study on reproducible UCNP synthesis by Andresen et al identified heating rate as a key parameter [34].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, both these hotplates have different temperature-cotrol logic which cannot be matched. Heating rate is known to be an important parameter in UCNP synthesis [69,70]. Indeed, a recent exemplary study on reproducible UCNP synthesis by Andresen et al identified heating rate as a key parameter [34].…”
Section: Resultsmentioning
confidence: 99%
“…A strong dependence on the size of upconversion NaYF 4 : Yb 3+ ,Er 3+ nanocrystals was observed; the larger the particles, the higher the emission (Schietinger et al, 2009), which also affects the synthesis strategy of UCNPs. Methods developed for the preparation of hexagonal-phase UCNPs with uniform size (Wang et al, 2012), which is advantageous for biomedical applications, include thermal decomposition (Xie et al, 2013), hydrothermal/solvothermal synthesis with phase transfer (Wang et al, 2009), microemulsion (Shan et al, 2011), sol-gel processing (Yao et al, 2016) and microwave synthesis (Egatz-Gomez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%